NCP2/RHD4/SAC7, SAC6 and SAC8 phosphoinositide phosphatases are required for PtdIns4P and PtdIns(4, 5)P2 homeostasis and Arabidopsis development. Issue 2 (16th May 2021) - Song, Lizhen; Wang, Yanning; Guo, Zhiai; Lam, Sin M.; Shui, Guanghou; Cheng, Youfa
Summary: Phosphoinositides play important roles in plant growth and development. Several SAC domain phosphoinositide phosphatases have been reported to be important for plant development. Here, we show functional analysis of SUPPRESSOR OF ACTIN 6 ( SAC6 ) to SAC8 in Arabidopsis, a subfamily of phosphoinositide phosphatases containing SAC‐domain and two transmembrane motifs. We isolated an Arabidopsis mutant ncp2 that lacked cotyledons in seedling and embryo in pid, a background defective in auxin signaling and transport. NCP2 encodes RHD4/SAC7 phosphoinositide phosphatase. SAC6, SAC7 and SAC8 exhibit overlapping and specific expression patterns in seedling and embryo. The sac6 sac7 embryos either fail to develop into seeds, or have three or four cotyledons. The embryo development of sac7 sac8 and sac6 sac7 sac8 mutants is significantly delayed or lethal, and the seedlings are arrested at early stages. Auxin maxima are decreased in double and triple sac mutants. The contents of PtdIns4P and PtdIns(4, 5)P2 in sac6 sac7 and sac7 sac8 mutants are dramatically increased. Protein trafficking of the plasma membrane (PM)‐localized protein PIN1 and PIN2 from trans ‐Golgi network/early endosome back to PM is delayed in sac7 sac8 mutants. These results indicate that SAC6–SAC8 are essential for maintaining homeostasis of PtdIns4P and PtdIns(4, 5)P2, and auxin‐mediated development in Arabidopsis.